A randomized clinical trial to stimulate the cholinergic anti-inflammatory pathway in patients with moderate COVID-19-pneumonia using a slow-paced breathing technique - Balint, Elisabeth Maria; Grüner, Beate; Haase, Sophia; Kaw-Geppert, Mandakini; Thayer, Julian F.; Gündel, Harald; Jarczok, Marc N. (Frontiers in Immunology, 2022)
Purpose: A characteristic problem occuring in COVID-19 is excessive elevations of pro-inflammatory cytokines (e.g. IL-6 and CRP) which are associated with worse clinical outcomes. Stimulation of the vagally-mediated cholinergic anti-inflammatory reflex by slow paced breathing with prolonged exhalation may present a clinically relevant way to reduce circulating IL-6. Method: Single-center randomized controlled clinical trial with enrolment of 46 patients hospitalized with confirmed severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection and moderate COVID-19 pneumonia (primary diagnosis). Differences between intervention (4sec inhalation, 6sec exhalation for 20 minutes 3x daily) and control group (TAU) in IL-6 calculated using multilevel mixed-effect linear regression models with random slope including the covariates relevant comorbidities, COVID-19 medication, and age. Results: Mean age was 57 years±13 years, N= 28 (60%) male, N=30 (65%) with relevant comorbidities. The model including group-by-time interaction revealed a significantly lower trajectory of IL-6 in the intervention group (effect size Cohens f2=0.11, LR-test p=.040) in the intention-to-treat sample, confirmed by treatment-per-protocol analysis (f2=0.15, LR-test p=.022). Exploratory analysis using the median split of practice time to predict IL-6 of the next morning indicated a dose-response relationship with beneficial effects of practice time above 45 minutes per day. Oxygen saturation remained unchanged during slow-paced breathing (95.1%±2.1% to 95.4%±1.6%). Conclusion: Patients practicing slow-paced breathing had significantly lower IL-6 values than controls with a small to medium effect size and without relevant side effects. Further trials should evaluate clinical outcomes and an earlier start of the intervention. Slow-paced breathing could be an easy to implement, low-cost, safe and feasible adjuvant therapeutic approach to reduce circulating IL-6 in moderate COVID-19 pneumonia. Trial registration: German register of clinical trials (ID: DRKS00023971) https://www.drks.de, Universal Trial Number (UTN) U1111-1263-8658;